Judges' Considerations In Deciding The Case Of Plasma Farmers Of Kud Minanga Ogan Oil Palm Plantation (Case Decision Number 38/Pdt/2021/Pt.Plg) - Farna Yunita*; Khalisah Hayyatudin; Helwan Kastra; Abdul Latif Mahfu (Universitas Syiah Kuala, 2023)
Consideration of judges is one of the components that is very important and necessary to make a decision on a case because the consideration is considered as the responsibility of judges to the community so that the decisions they make are considered objective by the community. The Village Unit Cooperative (KUD) Minanga Ogan has established cooperation with the Core Plantation Company, PT Minanga Ogan Plantation. It is known that PT. Minanga Ogan Plantation invaded the land owned by the Village Unit Cooperative (KUD) without the right and unlawful to control the land and establish a Palm Oil plantation on land owned by Aquo and for his actions brought harm to others therefore, in essence the Village Unit Cooperative (KUD) demands that PT. Minanga Ogan Plantation be declared to have committed an unlawful act that harms him and demands that he pay a sum of compensation as specified in the petitidum of his lawsuit. This research uses Normative legal research methods, research in this writing is done by means of literature study (library Research). Legal materials in this study secondary data and primary data. Primary data is the KUD Management and Law Enforcement Apparatus while secondary data in the form of Law No. 5 of 1960 on Basic Agrarian, Article 33 Paragraph (3) on land and Law No. 48 of 2009 on the power of acceptance.